Energy-Economic-Environmental assessment of solar-wind-biomass systems for finding the best areas in Iran: A case study using GIS maps. (October 2022) - Razavi Dehkordi, Mohammad Hossein; Meghdadi Isfahani, Amir Homayoon; Rasti, Ehsan; Nosouhi, Reza; Akbari, Mohammad; Jahangiri, Mehdi
Abstract: According to the existing capacities of solar and wind in Iran and given this fact that, to reach a proper economic growth, Iran needs to increasing its capacity in the generation of power, and also noting that there is a severe water shortage in Iran and Iran is required to produce power without water consuming, present paper attempts to find the minimum price of electricity production by hybrid wind-biomass-solar configurations in the 103 station of Iran, using NASA website data and hybrid optimization model for multiple energy resources (HOMER) software. Forasmuch as building sector counting for 45% of energy using in Iran, the goal of present study is supplying the electricity for off-grid/on-grid in homemade scale. The outcomes showed that in on-grid mode, the cost of generating electricity is less than that of the off-grid. In the off-grid biomass generator-based system, Bandarabbas and Jask with 0.519 $/kWh and 0.385 $/kWh, are the most suitable stations for wind turbine applications and solar cell applications, respectively. For on-grid mode, these prices are reduced by 65 to 80%. As a general result, it can be said that Bandarabbas, Jask and Bandarabbas stations are the most suitable for wind, solar and wind-solar hybrid respectively.